The Implications of Arendt's Concept of Judgment for Humanistic Teaching in a Postmetaphysical Age. Issue 6 (December 2015) - Kwak, Duck‐Joo
Abstract: In this essay, Duck‐Joo Kwak draws on Hannah Arendt's concept of judgment in exploring what it means to teach the humanities as a form of values education in a postmetaphysical age. Arendt's concept of judgment is closely related to Ciceronian humanism, which is concerned with the wisdom to choose one's company while appreciating this pursuit itself, among men, things, and thoughts from the past and present. According to Arendt, this wisdom as a form of judgment can be generated from a unique form of thinking via understanding. Thus, the main focus of this essay is on Arendt's explication of two distinct forms of humanistic thinking, which can be characterized as critical and interpretive, respectively. The educational virtue of humanistic thinking lies in its avoidance of both authoritarianism and nihilistic constructivism, both of which are problematic in the context of postmetaphysical contemporary culture, while also holding the potential to help young people find good company as a way of expanding the boundaries of intersubjectivity in their selfhood.